The Etheral plane of EU decision-making: the relationship between the European Council and the rule of law during the Eurozone and refugee crises - Fuente Bravo, Juan (Riga Graduate School of Law, 2018)
This paper aims to identify whether the European Council has respected the general principle of the rule of law during the actions taken during the Eurozone and refugee crises. The research is structured in three parts: first, a detailed overview of the intuitional formation of the European Council since its origins to the present day, with a closer look at the competences provided for by the Lisbon Treaty. Second, an analysis of the decision-making process of the European Council through the Eurozone and the refugee-management crisis, with more emphasis and detail dedicated to the second one, being far less researched that the first one.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law